Brazilian privatisation: The rocky path from state capitalism to regulatory capitalism - Andrea E. Goldstein (Fondazione Eni Enrico Mattei (FEEM), 1997)
Since the outset of the Real Plan, Brazil has made considerable progress in economic stabilisation, although privatisation has so far been incomplete. This study aims at answering a number of questions emerging from the Brazilian privatisation experience. To what extent have sell-offs been influenced by Brazil's legal and institutional framework and by its political context? How are authorities coping with the issues regarding ownership patterns and market structures? And, taking into account the key role that "state capitalism" has played in the country's development, what model of corporate organisation is emerging? The first section describes the history and the role of the Brazilian public enterprise sector. The second section sets out the policy, legal and operational framework in which privatisations were implemented, compares its features with those prevailing in other countries, and provides an updated account of state sell-offs. The following two sections analyse the consequences in terms of corporate governance and regulatory reform.
Keywords: H1; G3; L5; 330; Privatisierung; Eigentümerstruktur; Regulierung; Staatskapitalismus; Brasilien